Enabling and Impending Factors of NGOs in Karnali Zone, Nepal - Mahat, Kushendra Bahadur; Pokharel, Bihari Binod (Journal of Advanced Academic Research, 2017)
Introduction: Nongovernmental Organizations (NGOs) are one of the major parts of the Civil Society institutions to develop the nation. Government has established the separate social welfare act to register and operate to contribute their efforts as complementary support for addressing the basic development requirements of the community to synergic the joint efforts of the development stakeholders. The study was conducted in Midwestern Development Region of Karnali Zone in Nepal where Social Welfare Council and Donor communities are highly prioritized to mainstream into national development process.Objective: The objective of this research was to identify the enabling and impending factors of NGOs in Karnai Zone, Nepal.Methodology: This study was based on the pragmatism philosophy. The study had done 45 in-depth interview and 15 focus group discussion with key informants. Qualitative analysis was done to identify the enabling and impending factors of NGOs.Result: Nine factors find the enabling and 7 points impending in general. In enabling factors are the will power of the NGOs, donors are interested and their priority, structural factors, environmental, ethical, program based, policy and democratic practice in the institution. Similarly, impending factors were geographical factors, weak planning and implementation, dependency mentality, lack of trained human resources, inadequate coordination and socio-economic problem.Conclusion: Impending factors may cause the problem in performances of NGOs so it is necessary to minimize the effect of impending factors by addressing though policy and program.